“Relevantization” of Ulum al-Millah and its contribution to Islamization of human knowledge - Zain, Ibrahim Mohamed (Revelation and Science, IIUM, 2012)
This article focuses on “relevantization” of ÑUlËm al-Millah (Islamic Sciences). It claims that the major concern of this process is how to identify the permanent aspects of these sciences which are connected with the ideal values of Islam. This requires a deep knowledge of both the historical forms of these sciences and the principles upon which they were established. Though Ibn Khaldun’s classification of knowledge and his historical narrative were given a considerable space, yet the contributions of Islamization of Human Knowledge School were highly regarded in the process of relevantization. This draws our attention to the importance of systematization of values as main task behind the process of relevantization.